CLEAN SELF DILATATION (CSD): ITS ROLE IN PREVENTION OF REOCCURRENCE OF STRICTURE URETHRA - M. Akram Malik; Iftikhar Ahmed2 (Journal of University Medical & Dental College)
ABSTRACT Background: Stricture Urethra is a highly reoccurrent disease. Various treatment modalities were used to prevent its reoccurrence with variable success. Clean Self Dilatation (CSD) is one of the modalities being employed to prevent its reoccurrence. Objectives: To assess the acceptability and compliance for the CSD and its outcome. Study Design: Observational study. Setting: Department of Urology, Madina Teaching Hospital, University Medical & Dental College, Faisalabad. Methods: Study was conducted between 01-08-2008 to 30-06-2010. All patients with Stricture Urethra were included irrespective of their age. Retrograde Urethrogram was performed in all patients. Patients were treated with Optical Internal Urethrotomy (OIU), Anastomotic and Substitutional Urethro-Plasties. Patients were advised to perform CSD for 06 months with prescribed schedule and follow up was done for another 06 months. Success of procedure was measured as relief from symptoms. Results: Total numbers of patients were 55 with age range of 09-65 years. Forty Nine (89%) patients were compliant to the procedure. Direct trauma and instrumentation were the most common etiologies (58%), and 49% patients presented with urinary retention followed by lower urinary tract symptoms (20%). Thirty three (60%) patients were treated with OIU and length of stricture was < 1cm in 36.36% patients. Reoccurrence of stricture was 100% in those who did not accept the procedure and 50% in those who partially complied. Twenty nine out of 34 (86%) patients were disease free who compiled the procedure for 06 months. Urinary tract infection (25%) and bleeding per urethra (9%) were the complications. Conclusion: Clean Self Dilatation is a safe, cost effective and easy to perform procedure for the prevention of urethral stricture with good acceptability, compliance, better outcome and with few complications.